And the war came the slavery quarrel and the American Civil War - Meyers, Donald J. (Algora Pub., 2005)
"This detailed account of slavery in America, from Jamestown through the Civil War, explains its economic importance in the North as well as the South, its impact on the political dynamics of the Civil War, and the moral dilemmas it posed"--Provided by publisher.